Gestural Interaction with Three-Dimensional Interfaces; Current Research and Recommendations. (September 2017) - Varma, Vasudha; Nathan-Roberts, Dan
New methods of interacting with latest three-dimensional (3D) display technologies are rapidly being tested, however, it is not yet certain, which kinds of interaction design would be most suitable for users to manipulate and interact with 3D content. Physical gestures have been a natural and intuitive mode of interaction for human-human communication and ways to replicate this for human-machine communication is increasingly being explored. This proceeding attempts to review the current state of technology and the existing research on the use of gestural interaction with three-dimensional interfaces. The focus is on the use of hand-based gestures, the scope is to identify challenges and limitations of using gestures with 3D interfaces, and the goal is to find guidelines to select appropriate gestures to interact with 3D displays. The paper also highlights existing gaps and potential future research areas, in the technological and usability domains, that must be addressed before gestures can be used seamlessly with 3D interfaces.